2022
DOI: 10.3390/su14169856
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Experimental Study of Sustainable Reinforced Portland Cement Concrete and Geopolymer Concrete Beams Using Rice Husk Ash

Abstract: The ordinary Portland cement (PC) manufacturing process emits toxic carbon dioxide into the environment. Minimizing cement consumption in the construction industry is a major scholarly priority. This paper studies the comparison of reinforced Portland cement concrete and geopolymer concrete beams, in which rice husk ash (RHA) is used as a partial replacement for cement. The study aims to determine the optimum mix proportion of Portland cement concrete with RHA (PC-RHA) and geopolymer concrete with RHA (GC-RHA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
1
4
0
1
Order By: Relevance
“…Where: M u is the flexural capacity of the normal section of the tested beam, f c is the concrete compressive strength (MPa), f y is the tensile strength for steel (MPa), The parameters of each tested beam are substituted into the above equation to calculate the ultimate moment capacity Mu. The calculated and experimental results are listed in Table 5, together with results obtained by Thumrongvut et al [27]. It is observed that the predicted values of the beam's ultimate flexural capacity Mu are close to the experimental values, therefore the presented formula can be effectively applied to determine the ultimate capacity of GC flexural elements.…”
Section: Analytical Calculation Of Flexural Capacitysupporting
confidence: 53%
“…Where: M u is the flexural capacity of the normal section of the tested beam, f c is the concrete compressive strength (MPa), f y is the tensile strength for steel (MPa), The parameters of each tested beam are substituted into the above equation to calculate the ultimate moment capacity Mu. The calculated and experimental results are listed in Table 5, together with results obtained by Thumrongvut et al [27]. It is observed that the predicted values of the beam's ultimate flexural capacity Mu are close to the experimental values, therefore the presented formula can be effectively applied to determine the ultimate capacity of GC flexural elements.…”
Section: Analytical Calculation Of Flexural Capacitysupporting
confidence: 53%
“…Large amounts of CO 2 emission leads to the greenhouse effect and aggravates global warming. A large portion of the waste produced in the manufacturing process is dumped and disposed of in landfills, damaging the soil and causing environmental pollution [4]. Since the sustainable development model of the social economy has been proposed, the protection of the environment and ecology is required in the production, use, maintenance, and reuse of concrete [5].…”
Section: Introductionmentioning
confidence: 99%
“…Both FA and GGBS undergo suitable treatment processes before being utilized as geopolymer materials in construction projects [47]. In addition, other waste materials were used to produce GPC, such as rice husk ash [63], waste glass [64], palm oil fuel ash [65], ceramic waste [66], bagasse ash [39], illitic clay [67], Moroccan clays [68], clay minerals [69], and smectite clay [70], silica fume [65], waste clay brick [71], waste bricks powder [72], sewage sludge ash [73], and basalt powder [74]. Alkali-activated materials can generally be divided into two groups: (a) the high calcium system, where GGBS is a representative precursor and results in the formation of a C-A-S-H type gel as the main reaction product; and (b) the low calcium system, where class F FA and metakaolin are representative raw materials and produce N-A-S-H type gels within a three-dimensional network as the main reaction product [75].…”
Section: Introductionmentioning
confidence: 99%